Efficiently Releasing the Trapped Energy Flow in White Organic Light‐Emitting Diodes with Multifunctional Nanofunnel Arrays. (26th March 2015) - Zhou, Lei; Ou, Qing‐Dong; Li, Yan‐Qing; Xiang, Heng‐Yang; Xu, Lu‐Hai; Chen, Jing‐De; Li, Chi; Shen, Su; Lee, Shuit‐Tong; Tang, Jian‐Xin
<x xml:space="preserve">Abstract</x> White organic light‐emitting diodes (OLEDs) hold great promise for applications in displays and lighting due to high efficiency and superior white color balance. However, further improvement in efficiency remains a continuous and urgent demand due to limited energy flow extraction. A powerful method for drastically releasing the trapped energy flow in conventional white OLEDs is demonstrated by implementing unique quasi‐periodic subwavelength nanofunnel arrays (NFAs) via soft nanoimprinting lithography, which is ideal for enhancing light extraction without any spectral distortion or angular dependence. The resulting efficiency is over 2 times that of a conventional OLED used as a comparison. The external quantum efficiency and power efficiency are raised to 32.4% and 56.9 lm W−1, respectively. Besides, the substantial increase in efficiency over a broad bandwidth with angular color stability, the experimental proofs show that the NFA‐based extraction structure affords the enticing capacity against scrubbing and the self‐cleaning feature, which are critical to the commercial viability in practical applications.